The relationship between household expenditure and home ownership in determining affordability / Rohayu Ab Majid, Amir Saufi Norzin and Rosli Said - Ab Majid, Rohayu; Norzin, Amir Saufi; Said, Rosli (Research Innovation Business Unit, 2014)
Relationship between household expenditure and house ownership is a human need and becomes a dream for everybody especially the young couple those newly married. However, affordability issues are usually measured by the level of income which becomes an excuse for failing to have their own houses. In addition, high house prices are also seen as contributing factor to this problem. However, income levels and house prices are not the sole factors that could measure the house affordability. The ability to buy a home is not only dependent on house price and income level but also affected by financial structure that really based on good expenditure pattern. Young married couple can be referred as a group within age of 21 to 39 years old, which comprises of young adult with the capability to work and contribute to labour supply. Younger married couple tends to accumulate higher mean debt compared to older group of couple. However, Debts tend not to be regard as problematic unless repayment gets out of control. Consumption or expenditure pattern throughout the different stages of family life cycle could reflect the adjustment made by the household to meet the dynamic changes in raising a family; demand of growing family, educational needs, retirement plans and its own financial needs. Thus, this research aims to examine the spending patterns that could influence people’s affordability in home ownership among young people. A total of young household couple those aged 20 to 35 years in Selangor were interviewed to see how their income allocated to the various forms of expenditure, as well as the relationship between spending patterns and their ability to buy houses. Data were divided into 3 sets of data, in order to generate the significant value and analysed the relationship that exists between the various types of expenses and house ownership. The result shows that young people who already bought a house more likely to allocate their spending on saving and utilities. Those who do not own a house yet preferred their income on miscellaneous spending which involved unplanned groceries, shopping, dining-out, movies, clothing, grooming, women accessories and make up and fees for sport at gym. Thus, the issue of affordability among young couple should be taken into consideration the spending pattern that generate from their behaviour. This study has highlighted the pattern of household expenditure as the new aspect in benchmarking house affordability apart from current measurement.